2021
DOI: 10.1158/1055-9965.epi-20-1029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet and Exercise-Induced Weight Loss on Biomarkers of Inflammation in Breast Cancer Survivors: A Systematic Review and Meta-analysis

Abstract: Background: Adiponectin, leptin, and pro- and anti-inflammatory cytokines are implicated in breast cancer risk and recurrence. Weight loss, via the dynamic interplay of energy balance through exercise and/or caloric restriction, decreases risk of breast cancer recurrence. Methods: We investigated the effects of lifestyle modifications (exercise only, or combined caloric restriction and exercise) on adipokines, IL2, IL6, IL8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 58 publications
5
18
0
1
Order By: Relevance
“…In addition, decreased CRP levels were observed among breast cancer survivors who engaged in weight loss programs in a few intervention studies, 30–32 but not in all 33,34 . A meta‐analysis on the effect of weight loss intervention on inflammatory biomarkers among breast cancer survivors did not show a significant improvement in the levels of CRP, IL‐6, IL‐8, TNF‐α, and adiponectin 20 . However, a recent weight‐loss trial of overweight/obese breast cancer survivors reported that the levels of IL‐6 and adiponectin were improved after 6 months of weight loss intervention 35 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, decreased CRP levels were observed among breast cancer survivors who engaged in weight loss programs in a few intervention studies, 30–32 but not in all 33,34 . A meta‐analysis on the effect of weight loss intervention on inflammatory biomarkers among breast cancer survivors did not show a significant improvement in the levels of CRP, IL‐6, IL‐8, TNF‐α, and adiponectin 20 . However, a recent weight‐loss trial of overweight/obese breast cancer survivors reported that the levels of IL‐6 and adiponectin were improved after 6 months of weight loss intervention 35 .…”
Section: Discussionmentioning
confidence: 94%
“…33,34 A meta-analysis on the effect of weight loss intervention on inflammatory biomarkers among breast cancer survivors did not show a significant improvement in the levels of CRP, IL-6, IL-8, TNF-α, and adiponectin. 20 However, a recent weight-loss trial of overweight/obese breast cancer survivors reported that the levels of IL-6 and adiponectin were improved after 6 months of weight loss intervention. 35 In addition, that study showed increased levels of leptin and IL-6 after weight regain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite adiposity being a theoretically modifiable factor related to inflammation, a recent meta-analysis suggests that interventions targeting adiposity (i.e., physical activity, caloric restriction, weight management) do not significantly decrease inflammatory cytokines, including IL-6 and TNF-α, in BC survivors [33]. Another modifiable factor related to inflammation is stress [34].…”
Section: Introductionmentioning
confidence: 99%